Integrated Business and Engineering Educational Experience for Medical Students in the Development of Pediatric Medical Devices - Jennifer J. Li; Jonathan Lee; Mayilone Sathialingam; Nhi Ha; Tamara Galoyan; Ethan Faye; Michael Kim; Tara Shelby; Rishabh Shah; Yelim Lee; Melissa Bent; Juan C. Espinoza (Journal of Medical Education and Curricular Development)
BACKGROUND There are few opportunities in undergraduate medical education that provide formal training in engineering and scientific innovation. Institutions have sought to address student-specific career goals through combined degree programs such as the Medical Scientist Training Program and MD/MBA. However, only a small percentage of medical students pursue these additional degrees. Partnerships between medical schools and Medical Technology (MedTech) accelerators may create unique opportunities for medical students to gain real-world experience with scientific innovation and entrepreneurship. METHODS An internship program was developed by the Keck Translational Biotechnology Association and the West Coast Consortium for Technology & Innovation in Pediatrics (CTIP), a Food and Drug Administration-funded pediatric medical device accelerator. Students and companies applied to participate and were paired based on students’ interests and experience, and project plans were developed together. An initial orientation provided an overview of the program structure and expectations. Students and mentors met biweekly to address questions or concerns surrounding the progress of their projects. Students gave final project presentations and completed program evaluations. Data from 3 iterations of the program are reported. RESULTS Student program satisfaction was measured across 5 domains. Students felt that working with CTIP was valuable to their education (mean score = 3.7 of 5.0) and encouraged them to pursue future careers in MedTech (mean score = 4.0 of 5.0). Students provided a few suggestions to improve the program, including more structure, clear expectations around time commitment and deliverables, and stipends for students. Participation in the program grew over time. CONCLUSIONS The initial iterations of the internship program were well received by students. Several opportunities for improvement were noted. The program grew over time. Partnerships with accelerator programs at medical schools and academic medical centers may provide key real-world opportunities for students to learn about MedTech.